A case of anti‐laminin gamma‐1 (p200) pemphigoid with bullous lesions on the lips, hands and feet showing antibodies to desmoglein 1 - F. Kaneko; M. Ozasa; A. Togashi (Wiley, 2022)
Abstract An 87‐years‐old‐man presented with bullous and erosive lesions exclusively on the lips, hands and feet. Histopathological and direct immunofluorescence studies suggested the diagnosis of bullous pemphigoid, but the serum anti‐BP180 antibodies were negative. Strangely, anti‐desmoglein 1 antibodies were positive, although no pemphigus‐like features were found. Indirect immunofluorescence showed IgG reactivity with dermal side of 1 M NaCl‐split skin. Immunoblotting showed positive reactivity with the 200 kDa laminin gamma‐1 but not with type VII collagen. After the administration of prednisolone 20 mg/day, bullous lesions cleared within 2 weeks.